Test to Determine The Quercetin Content of Tenggiang (Polystichum setiferum) Using the High Performance Liquid Chromatography (HPLC) Method and Its Antifungal Activity Against Pityrosporum ovale - Turnip, Nur Ulina M. Br.; Ratih Anggraeni; Sihombing, Yanna Rotua; Suci Wulandari (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Indonesia is a country with high temperature and humidity, which are supporting factors for the development of microbes. One of the microbes that causes infection is the fungus Pityrosporum ovale which can cause dandruff, especially on the scalp. Treatment is usually done using shampoo containing an antidandruff formula. Synthetic chemicals used in hair care have been widely known and used to treat various infections caused by fungi. Tenggiang, a shrub originating from the Toba Samosir area, is used empirically as a wound medicine. In previous studies, Tenggiang has been shown to have antimicrobial, antioxidant, and anti-inflammatory effects. This is related to the content of secondary metabolites found in tenggiang, such as flavonoids, terpenoids/steroids, saponins, and phenolics. Flavonoids, which are secondary metabolites of the polyphenol group. Objective: to measure the levels of quercetin in tenggiang using the HPLC method and to evaluate its antifungal activity against Pityrosporum ovale. Method: measurement of quercetin using the HPLC method and measurement of antifungal activity using the Kirby-bauer method. Results: The measurement results were then calculated as quercetin equivalents, the extract contained a total of 1.33% flavonoids. The retention time data of the standard quercetin was 5.405 minutes and the retention time of the ethanol extract of mackerel was 5.332. The ethanol extract of mackerel was said to contain quercetin because it had a retention time that was relatively the same as the retention time of the standard quercetin. The extract also showed potential as an antimicrobial agent, where an increase in extract concentration was directly proportional to an increase in the diameter of the inhibition zone. In addition, when compared to the blank, the resulting difference was statistically significant (p <0.05). Conclusion: Tenggiang, extract has antifungal activity and antioxidant potential.